The Effect of Back Massage Using VCO (Virgin Coconut Oil) on Sleep Quality in the Elderly in Banjar Jambe Working Area of UPTD Puskesmas Utara - Mahayoni, Anak Agung Ayu Agung Istri; Sari, Ni Luh Putu Dian Yunita; Martini, Ni Made Dwi Ayu; Wulandari, Ni Putu Dita (Universitas Ibn Khaldun Bogor, 2024)
Poor sleep quality has physiological and psychological consequences, including weakness, elevated blood pressure, decreased activity, diminished endurance, emotional instability, and withdrawal. Sleep quality can be assessed using the Pittsburgh Sleep Quality Index questionnaire. Many things can be done to improve sleep quality in the elderly, one of which is back massage combined with VCO (Virgin Coconut Oil). This research aims to determine the effect of back massage using VCO (Virgin Coconut Oil) on sleep quality in the elderly. This is a pre-experimental study with a one-group pre-and post-test design. The sample for this study was drawn using a non-probability sampling technique, namely purposive sampling of 28 senior respondents who reported poor sleep quality. In bivariate analysis, the Wilcoxon signed rank test was employed to compare pretest and posttest scores. Based on the results of data analysis using the Wilcoxon Signed Range Test at a significance level of α = 0.05, a p-value of 0.000 < 0.05 was obtained. This shows that there is an effect of back massage using VCO (Virgin Coconut Oil) on sleep quality in the elderly in Banjar Jambe, Region Area of UPTD Puskesmas Kuta Utara. It is hoped that this research can be used for health services, nursing education and the community to overcome sleep disorders in the elderly.